(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: An ileostomy is a surgical procedure in which the small intestine (Ileum) is diverted through an opening in the abdominal wall, creating a stoma to allow waste to bypass the colon and exit the body. Early and conventional closure of ileostomy stomas are strategies to restore bowel continuity after temporary diversion. Early closure, performed within weeks, may reduce complications like dehydration and enhance recovery, while conventional closure, typically after 8-12 weeks, minimizes risks of anastomotic failure. Optimal timing balances patient safety and recovery outcomes. To assess the differences between the standard stoma closure and early stoma closure after a temporary covering ileostomy stoma and the post-operative results of them. Materials and methods: This quasi-experimental investigation was carried out throughout September 2021 to August 2022. There were 66 patients with temporary covering ileostomies in all, 33 of whom had early closure while the remaining 33 received traditional stoma closure. Patients were monitored after surgery on the first, fifth, and eighth postoperative days, as well as for two weeks after the index procedure. Results: All the patients were evaluated for wound infection, abdominal distension, anastomotic leakage and Length of Hospital stay (LoH) post operatively. The overall complications were in 1 st POD (12% vs 33.3%, p=0.039), 5 th POD (21.2% vs 36.4%, p=0.174 ns), 8 Th POD (21.2% vs 33.3%, p=0.268 ns ) after after 2 weeks (6.1% vs 27.3%, p=0.020). LoH was (93.9% vs 69.7%, p=0.010). Conclusion: Early closure group showed less complications then conventional closure group. More patients stayed at hospital less then 10 days post operatively in early closure group. So it can be said that early ileostomy closure is possible and can be done to reduce morbidity in patients. JCMCTA 2024 ; 35 (2) : 164-169